PERBEDAAN BEBAN KERJA, STRES KERJA DAN KINERJA KARYAWAN BERDASARKAN JENIS KELAMIN PADA KARYAWAN PT. POS KCU MAKASSAR - Melati , Bunga Harum; Suhartini, Eka; Abdullah, Wahidah (Study of Scientific and Behavioral Management, 2025)
This study aims to determine the differences in workload between female and male employees of PT. Pos KCU Makassar, differences in work stress between female and male employees of PT. Pos KCU Makassar, and differences in performance between female and male employees of PT. Pos KCU Makassar. This study uses quantitative research with a comparative/comparative research approach. The instrument in this study is by using a questionnaire. The data analysis technique in this study is the independent sample t-test processed using the SPSS 29.0 for windows program. The results of the two independent sample t-test are that there are differences in workload between male and female employees of PT. Pos KCU Makassar, there are differences in work stress between male and female employees of PT. Pos KCU Makassar, and there is no difference in employee performance between male and female employees of PT. Pos KCU Makassar.